Operations Intern - Baldewa, Sayong (ATLAS SkillTech University, 2024)
This internship report provides an overview of my experiences as an Operations Intern at Bhagirath synthetics. I took an active part in a wide range of operational activities throughout the period of two months, which helped me develop professionally and enhance my skills. As an Operations Intern, my primary focus was on optimizing supply chain management to enhance the efficiency of shipments. The field of supply chain management has gained immense importance in today's competitive business landscape. Efficient supply chain operations are crucial for reducing costs, improving customer satisfaction, and gaining a competitive advantage. Therefore, my objective was to explore the existing supply chain processes at Bhagirath synthetics, identify potential areas for improvement, and develop strategic recommendations or follow steps to streamline operations.
Project Report on Operations Intern (2022-24) Under the Guidance of Prof. David Wittenberg
Keywords: Operations